Combined pulmonary tuberculosis with pulmonary and pleural cryptococcosis in a patient receiving ruxolitinib therapy - Akarawut Kasemchaiyanun (2022)
With an advance in therapy, there are increasing emerging and re-emerging opportunistic infections among patients with hematologic conditions and malignancy. Herein, we present a 56-year-old woman with primary myelofibrosis who developed combined tuberculosis (TB) and cryptococcosis with extensive pulmonary, pleural, and nodal involvement during ruxolitinib therapy. Marked clinical and radiologic improvements were undoubtedly evident after receiving anti-TB and antifungal therapies and pleural drainage. Hence, the presence of atypical clinical and radiologic manifestations and incomplete responses, despite receiving adequate antimicrobial treatment, should raise concerns regarding the combined emerging and re-emerging opportunistic infections and the possibility of unusual radiologic manifestations of cryptococcosis in a ruxolitinib-treated patient.